THE TRAINING IN TEMPERATURE AND HUMIDITY CONDITIONING EQUIPMENT UTILIZATION FOR THE OYSTER MUSHROOM CULTIVATION BUSINESS AT PONGANGAN GUNUNGPATI - Utomo, Mardi Siswo; Sukur, Muji; Nurraharjo, Eddy; Nofiyanto, Erwin (LPPM Univ. Ibn Khaldun Bogor, 2023)
Oyster mushroom farming is a business practice for six SMEs in the Pongangan Gunungpati region. The fact that the production tools still in use are basic presents one of the main challenges to oyster mushroom cultivation. The production scale for fresh oyster mushrooms is still quite limited, and it has not been able to satisfy market demand. Additionally, production standards and good crop management have not been adopted. Among MSME members, production management and marketing management are still conducted independently, so that the circulation of fresh mushroom production and marketing is not optimal. Changes in climate and seasons are difficult to foresee and have a propensity to occur, and the popular perception that mushroom cultivation is difficult and can only be done in the highlands contributes to the low level of interest in mushroom farming. The inability of mushroom farmers to condition the mushroom house in accordance with applicable regulations and the absence of technology capable of maintaining stable temperature and humidity in the mushroom house area. Currently, mushroom growers in the Pongangan subdistrict still utilize a rudimentary irrigation mechanism and manually water their crops each morning and evening. The objective of the performed service activities is to use appropriate technology to condition the air’s temperature and humidity to match the natural circumstances of oyster mushrooms.